The characterisation and water equivalency of rhizophora spp. particleboard bonded with soy protein - Rabaiee, Nor Ain; Abdul Aziz, Mohd Zahri; Hashim, Rokiah (UNIMAS Publisher, 2021)
The objective of this study was to explore the potential of particleboard made from a type of mangrove hardwood, i.e. Rhizophora spp., bonded with soy protein, and evaluate its suitability as a water-equivalent material. First, the bark of the raw hardwood was removed from its trunk prior to the grinding process. Next, three particleboards were fabricated with different percentages of soy protein (0 %, 8 %, and 16 %). The fabricated particleboards were each characterised for their density, mechanical properties, effective atomic number, morphological structure, elemental composition and probability of photon interaction. The dimensional stability of each fabricated particleboard was evaluated according to the Japanese Industrial Standard (JIS) A 5908, Type-8, while the other properties were compared with that of the standard water phantom. There were improvements shown by the fabricated particleboards with 8 % and 16 % soy protein, in terms of dimensional stability. The morphological images also revealed that the particleboards bonded with 8 % and 16 % soy protein, have better contact between the particles, compared to the one bonded with 0 % soy protein. The elemental analysis, effective atomic number, and probability of photon interaction of the fabricatedphantom showed identical results with that of the standard water phantom. Based on the findings of this study, the Rhizophora spp. particleboard bonded with soy protein has opened up possibilities for another potential alternative of solid phantom material as water-equivalent material.